The Effect Of Service Quality And Price On Customer Satisfaction At Cv. Abadi Steel Lahat - Dzaka Dwi Pangestu; Titi Hasanah; Marko Ilpiyanto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to analyze the effect of promotion costs and pricing on sales volume growth at Panca Logam Building Store in Tebing Tinggi, Empat Lawang Regency. The findings indicate that promotion costs (X₁) have a positive and significant effect on sales volume (Sig. = 0.008 < 0.05). Similarly, pricing (X₂) also has a positive and significant effect on sales volume (Sig. = 0.016 < 0.05). Simultaneously, both variables significantly affect sales volume, with a coefficient of determination (R²) of 0.751, meaning that 75.1% of the variation in sales volume can be explained by promotion costs and pricing, while the remaining 24.9% is influenced by other factors outside this study. Thus, effective promotional strategies and competitive pricing are proven to enhance sales performance in building material stores.